Effect of Genetic and Non-genetic Factors on Lactation Traits in Jersey x Sahiwal Crossbred Cattle under Progeny Testing Programme of Chittoor - Mohammad Siraj, Shaik; Venkata Subramanyam, Boddu; Sakunthala Devi, Kopparthi; Suresh Babu, Dasineni; Vani, Sunkara; Eswar Bhavani, Killana (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Data on lactation traits collected from first lactation performance records of 4,877 daughters sired by 176 Jersey x Sahiwal crossbred  bulls, maintained by selected field farmers under field Progeny Testing Programme across 24 mandals in Chittoor district, Andhra  Pradesh (India), over a period of 10 years (2014 to 2023) were used for genetic analysis of lactation traits viz. 305-day milk yield (305DMY),  total milk yield (TMY), lactation length (LL) and peak yield (PY). The overall least-square means for these traits were 2276.46±8.57 kg,  2300.23±9.20 kg, 283.93±0.49 days and 10.23±0.03 kg, respectively. The effect of sire, period and season of calving were found to be  highly significant (p
Keywords: Genetic and non-genetic factors; Genetic and Phenotypic correlations; Heritability; Jersey x Sahiwal crossbred cattle